EFEKTIFITAS PENYEMBUHAN GANGGUAN JIWA KOLABORASI METODE RUQYAH DAN HIPNOTERAPI DI LEMBAGA EL-PSIKA AL-AMIEN PRENDUAN - Irfan Akbar Rahmatullah (Al-Amien Prenduan for Islamic Institute, 2021)
In this area, there are many kind of mental disorder befalls unto people, the problem is people are difficult to solve or get way out from that problem. Finally it is being allowed because they cannot find the way to recover it. So the effect gets worst and then motivate them to hurt other or them selves. So the aim of this research is to give solution for them who where being affected by supranatural, mentality, physical, psychology, and spiritual disorder. With giving double recovering treathment, they are the collaboration of ruqyah method and hypnoterapi method in eL-PsikA Foundation Al-Amien Prenduan.